2020
DOI: 10.1021/acsami.0c06701
|View full text |Cite
|
Sign up to set email alerts
|

3D Interconnected Gyroid Au–CuS Materials for Efficient Solar Steam Generation

Abstract: Surface plasmon resonance (SPR), a promising technology, is beneficial for various applications, such as photothermal conversion, solar cells, photocatalysts, and sensing. However, the SPR performance may be restricted by the 1D-or 2D-distributed hotspots. The bicontinuous interconnected gyroidstructured materials have emerged in light energy conversion due to a high density of 3D-distributed hotspots, ultrahigh light− matter interactions and large scattering cross-section. Here, a series of bioinspired Au−CuS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 50 publications
0
38
0
Order By: Relevance
“…Recent research on generating solar steam has focused primarily on exploring photothermal materials with high absorption in the solar spectrum. Many researchers have investigated plasmonic absorbers [29] and noble metallic and nonmetallic nanoparticles such as NiO nanoparticles, [30] MoS 2 nanosheets, [31][32][33][34] processed wood, [35][36][37] activated carbon, [38,39] carbon nanotube, [40][41][42] carbon black, [43][44][45] carbon foam, [43,[45][46][47] carbon fiber, [48][49][50] graphene and graphene oxide, [39,[51][52] Au nanoparticles [53][54][55][56][57] on finding efficient photothermal conversion materials for the top layer to absorb the incident solar irradiation and convert it into heat energy. Many research groups [58][59][60][61] demonstrated the use of 3D porous graphene/carbon hybrid aerogels as photothermal material and achieved significantly higher photothermal efficiency under 1 sun (1 sun = 1 kW m −2 ) illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research on generating solar steam has focused primarily on exploring photothermal materials with high absorption in the solar spectrum. Many researchers have investigated plasmonic absorbers [29] and noble metallic and nonmetallic nanoparticles such as NiO nanoparticles, [30] MoS 2 nanosheets, [31][32][33][34] processed wood, [35][36][37] activated carbon, [38,39] carbon nanotube, [40][41][42] carbon black, [43][44][45] carbon foam, [43,[45][46][47] carbon fiber, [48][49][50] graphene and graphene oxide, [39,[51][52] Au nanoparticles [53][54][55][56][57] on finding efficient photothermal conversion materials for the top layer to absorb the incident solar irradiation and convert it into heat energy. Many research groups [58][59][60][61] demonstrated the use of 3D porous graphene/carbon hybrid aerogels as photothermal material and achieved significantly higher photothermal efficiency under 1 sun (1 sun = 1 kW m −2 ) illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Pollutants in the water can be effectively removed using solar energy to provide fresh water and alleviate the shortage of freshwater . So far, many light-to-heat conversion materials have been developed, such as plasma materials, carbon-based materials, semiconductor materials, and polymer materials for solar steam generation. Although significant achievements have been made in the preparation of photothermal materials in the past few years, the problem still exists; in some cases, high costs (due to use of metals like gold and silver), harsh conditions (such as high-temperature carbonization, freeze-drying, or plasma treatment), or the use of photothermal materials and special equipment materials hinder industry applications.…”
Section: Introductionmentioning
confidence: 99%
“…Solar steam generation has gained more attention in seawater desalination and wastewater purification because it can harvest solar light and generate heat at the water-air interface. [1][2][3][4] Traditionally, three crucial principles should be considered to design high-performance solar steam generation devices: 1) constructing photothermal materials with broadband absorption capacity; 2) reducing heat loss at the evaporative region; and 3) providing effective water transport by channel structures to improve evaporation rate. [5,6] Various solar absorption materials, such as metal particles, [7,8] semiconductor materials, [9] and carbonbased materials such as graphene-related materials [10,11] and carbon anotubes, [12,13] have been exploited as photothermal agents because of their high solar-to-thermal conversion performance.…”
Section: Introductionmentioning
confidence: 99%